Understanding caregivers' needs: supporting families of autistic children - John, Leena Pravil; Hemalatha, R. (International Journal Of Community Medicine And Public Health, 2024)
Parenting a child with autism spectrum disorder (ASD) poses significant emotional, financial, and social challenges to caregivers. This paper examines the experiences of caregivers, highlighting their increased stress, burnout, and mental health concerns. The importance of accessible information resources, respite care services, emotional support networks, and financial assistance programs is emphasized. Effective strategies for supporting caregivers include educating them about ASD symptoms, treatments, and therapies, teaching coping mechanisms for managing challenging behaviors, and promoting collaboration between healthcare providers and caregivers. Policy implications are discussed, including advocating for legislative modifications that prioritize caregiver needs, promoting inclusionary practices within educational systems, and increasing funding for early intervention programs and caregiver support services. The implementation of parent training programs, collaborative relationships between educators and caregivers, and professional development opportunities for educators are also recommended. This study aims to inform policymakers, healthcare professionals, and educators about the critical role of caregiver support in improving outcomes for children with ASD. By addressing caregiver needs and providing comprehensive support, we can enhance the well-being of both caregivers and children with ASD.